2016
DOI: 10.1002/cam4.709
|View full text |Cite
|
Sign up to set email alerts
|

Elevated microsatellite alterations at selected tetranucleotides in early‐stage colorectal cancers with and without high‐frequency microsatellite instability: same, same but different?

Abstract: Microsatellite instability (MSI) is associated with better prognosis in colorectal cancer (CRC). Elevated microsatellite alterations at selected tetranucleotides (EMAST) is a less‐understood form of MSI. Here, we aim to investigate the role of EMAST in CRC±MSI related to clinical and tumor‐specific characteristics. A consecutive, population‐based series of stage I–III colorectal cancers were investigated for MSI and EMAST using PCR primers for 10 microsatellite markers. Of 151 patients included, 33 (21.8%) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 28 publications
3
43
0
Order By: Relevance
“…MSI analysis was performed using a panel of three mononucleotide markers: BAT‐25, BAT‐26, and NR‐27 and EMAST analysis was performed using a panel of five tetranucleotide markers: D20S82, D20S85, D9S242, D8S321, and MYCL1. Polymerase chain reaction (PCR) was performed with previously described primers (Mojarad et al, ; M. M. Watson et al, ) without fluorescent labels. Amplification reactions (25 μl) were prepared subjected to PCR amplification: Initial incubation at 95°C for 5 min, followed by 35 cycles of 95°C for 40 s, 62°C for 40 s, and 72°C for 40 s, and a final incubation at 72°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…MSI analysis was performed using a panel of three mononucleotide markers: BAT‐25, BAT‐26, and NR‐27 and EMAST analysis was performed using a panel of five tetranucleotide markers: D20S82, D20S85, D9S242, D8S321, and MYCL1. Polymerase chain reaction (PCR) was performed with previously described primers (Mojarad et al, ; M. M. Watson et al, ) without fluorescent labels. Amplification reactions (25 μl) were prepared subjected to PCR amplification: Initial incubation at 95°C for 5 min, followed by 35 cycles of 95°C for 40 s, 62°C for 40 s, and 72°C for 40 s, and a final incubation at 72°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is a link between MSI and immune response in that previous studies have found that patients with MSI have a higher percentage of CD8 + T-cells, but a lower percentage of CD4 + T-cells in tumour compared to those with microsatellite stable (MSS) disease (16). Another form of MSI includes elevated microsatellite instability at selected tetranucleotide repeats (EMAST) (17), which has been associated with a higher density of CD8 + at tumour nests (18) and was included together with MSI in this study for comparison.…”
Section: Conclusion: There Is a Correlation Between Blood Cd3 + And Cmentioning
confidence: 99%
“…In colorectal cancer, the incidence of EMAST was similar to that of MSI and was approximately 20%-40%; EMAST+ tumors were associated with the MSI-H phenotype and more frequently located in the colon than in the rectum [5,6]. However, in non-small cell lung cancer [7], the incidence of EMAST was higher than that of MSI (42.9% vs. 16.3%), and there was no association between the incidence rates of EMAST and MSI.…”
Section: Introductionmentioning
confidence: 95%
“…However, in non-small cell lung cancer [7], the incidence of EMAST was higher than that of MSI (42.9% vs. 16.3%), and there was no association between the incidence rates of EMAST and MSI. The correlation between EMAST status and patient survival in cancer is still controversial [5][6][7][8]. Consequently, there is a need to investigate the correlation among EMAST status, MSI status, genetic alterations, and clinicopathological features in GC patients.…”
Section: Introductionmentioning
confidence: 99%